The Combination Therapy of Self-Surrender Exercise and Distraction Against Osteoarthritis Pain Scale of Elderly In Coastal Area - Syaifurrahman Hidayat; Elyk Dwi Mumpuningtias; Ratna Indriyani (Universitas STRADA Indonesia, 2020)
A combination therapy of resignation and distraction techniques builds on relaxation. For this reason, this study aims to provide a combination therapy of self-surrender training (LPD – latihan pasrah diri in bahasa) and distraction techniques to reduce the scale of osteoarthritis pain in Madurese elderly in coastal areas. The research method used was quasi-experimental. The sample of the study was elderly who experience osteoarthritis pain in coastal areas, with a purposive sampling technique using the inclusion and exclusion criteria approach, with a total sample of 70 elderlies. Data were analyzed using the Wilcoxon Signed Ranks and Mann-Whitney Test. The results of this study indicate that the combination therapy of self-surrender training and distraction techniques is effective in reducing the level of osteoarthritis pain in the elderly living in coastal areas. The relaxing activity can be done both inside and outside the homes of the elderly who are mostly coastal areas